Real-time digital processing of GPS measurements for transmission engineering. - Mensah-Bonsu, C. (IEEE Transactions on power delivery)
The Global Positioning System (GPS) is a state-of-the-art timing and positioning system based on 24 or more satellites launched and maintained by the US government. Power engineering applications based on GPS include phasor measurement, positioning applications, such as surveying and mapping, and potentially in deriving real-time data on transmission lines that will allow them to be loaded to a dynamic (thermal or security) limit. Inherent errors in GPS technologies are discussed, and the differential GPS method is described for accuracy enhancement. Further digital-processing needs are necessary for meeting the accuracy requirements of certain specific applications. The focus of this paper is on the digital signal processing (DSP) of differential-GPS (DGPS) measurements. The paper describes a methodology for further improving DGPS altitude measurements for the purpose of accurate determination of high-voltage overhead conductor sag. The Haar wavelet transforms (HWT) and least-squares parameter estimation (LSPE) techniques are considered.